Caracterizacao climatica e variacao das disponibilidodes de agua nos nucieos canavieriros paulistas. - Dos Santos, M. J Z (My University, 1985)
Analyses water budgets and time series data on the relationship between rainfall and evapotranspiration for the sugar-cane zones of Sao Paulo State and then compares water availability in soil with agricultural yields. -R.N.Gwynne
Climatic characterization and variations in available water in sugar-cane zones in Sao Paulo State